TRPA1 Channels in Drosophila and Honey Bee Ectoparasitic Mites Share Heat Sensitivity and Temperature-Related Physiological Functions - Peng, Guangda; Kashio, Makiko; Li, Tianbang; Dong, Xiaofeng; Tominaga, Makoto; Kadowaki, Tatsuhiko (Frontiers in Physiology, 2016)
The transient receptor potential cation channel, subfamily A, member 1 (TRPA1) is conserved between many arthropods, and in some has been shown to function as a chemosensor for noxious compounds. Activation of arthropod TRPA1 channels by temperature fluctuations has been tested in only a few insect species, and all of them were shown to be activated by heat. The recent identification of chemosensitive TRPA1 channels from two honey bee ectoparasitic mite species (VdTRPA1 and TmTRPA1) have provided an opportunity to study the temperature-dependent activation and the temperature-associated physiological functions of TRPA1 channels in non-insect arthropods. We found that both mite TRPA1 channels are heat sensitive and capable of rescuing the temperature-related behavioral defects of a Drosophila melanogaster trpA1 mutant. These results suggest that heat-sensitivity of TRPA1 could be conserved between many arthropods despite its amino acid sequence diversity. Nevertheless, the ankyrin repeats (ARs) 6 and 7 are well-conserved between six heat-sensitive arthropod TRPA1 channels and have critical roles for the heat activation of VdTRPA1.